What Hedge Funds Really Do : An Introduction to Portfolio Management. - Romero, Philip J.; Balch, Tucker (New York : Business Expert Press, 2014)
When I managed a hedge fund in the late 1990s, computer-basedtrading was a mysterious technique only available to thelargest hedge funds and institutional trading desks. We've comea long way since then. With this book, Drs. Romero and Balch liftthe veil from many of these once-opaque concepts in high-techfinance. We can all benefit from learning how the cooperationbetween wetware and software creates fitter models. This bookdoes a fantastic job describing how the latest advances in financialmodeling and data science help today's portfolio managerssolve these greater riddles. --Michael Himmel, ManagingPartner, Essex Asset ManagementI applaud Phil Romero's willingness to write about the hedgefund world, an industry that is very private, often flamboyant,and easily misunderstood. As with every sector of the investmentlandscape, the hedge fund industry varies dramaticallyfrom quantitative "black box" technology, to fundamental researchand old-fashioned stock picking. This book helps investorsdistinguish between these diverse opposites and understandtheir place in the new evolving world of finance. --Mick Elfers,Founder and Chief Investment Strategist, Irvington Capital.
Cover -- Contents -- Part I: The Basics -- Chapter 1: Introduction -- Chapter 2: So You Want to Be a Hedge Fund Manager -- Chapter 3: An Illustrative Hedge Fund Strategy: Arbitrage -- Chapter 4: Market-Making Mechanics -- Chapter 5: Introduction to Company Valuation -- Part II: Investing Fundamentals: CAPM and EMH -- Chapter 6: How Valuation Is Used by Hedge Funds -- Chapter 7: Framework for Investing: The Capital Asset Pricing Model (CAPM) -- Chapter 8: The Efficient Market Hypothesis (EMH)-Its Three Versions -- Chapter 9: The Fundamental Lawof Active Portfolio Management -- Part III: Market Simulation and Portfolio Construction -- Chapter 10: Modern Portfolio Theory: The Efficient Frontier and Portfolio Optimization -- Chapter 11: Event Studies -- Chapter 12: Overcoming Data Quirks to Design Trading Strategies -- Chapter 13: Data Sources -- Chapter 14: Back Testing Strategies -- Part IV: Case Study and Issues -- Chapter 15: Hedge Fund Case Study: Long Term Capital Management (LTCM) -- Chapter 16: Opportunities and Challenges for Hedge Funds -- Teaching Cases -- Glossary -- Summary -- Index -- Ad page -- Cover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Hedge funds; Portfolio management; Electronic books